2015
DOI: 10.1159/000430195
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Approach for the Identification of HNF4α-Centered Transcriptional Regulatory Networks During Early Liver Regeneration

Abstract: Background/Aims: Hepatocyte nuclear factor-4α (HNF4α), the liver enriched transcription factor (TF), is one of the major regulators of hepatocyte differentiation and proliferation. However, how HNF4α participate in liver regeneration after partial hepatectomy (PH) remains largely unknown. In order to identify the HNF4α-centered regulatory network, we applied an integrated analytic strategy, in which, TF array, mRNA microarray, bioinformatic analysis and ChIP-on-chip assays were integrated. Methods/Results: The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 29 publications
3
10
0
Order By: Relevance
“…We also observed decreased HNF4α activity as measured by its target gene expression . Our observations independently reproduce a microarray study describing decreased HNF4α target gene expression 4 hours post‐PH . This highlights functional differences between quiescent and proliferating hepatocytes and suggests that restoring HNF4α in hepatocytes responding to chronic injury could successfully restore hepatic function .…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…We also observed decreased HNF4α activity as measured by its target gene expression . Our observations independently reproduce a microarray study describing decreased HNF4α target gene expression 4 hours post‐PH . This highlights functional differences between quiescent and proliferating hepatocytes and suggests that restoring HNF4α in hepatocytes responding to chronic injury could successfully restore hepatic function .…”
Section: Discussionsupporting
confidence: 83%
“…(12) Our observations independently reproduce a microarray study describing decreased HNF4α target gene expression 4 hours post-PH. (43) This highlights functional differences between quiescent and proliferating hepatocytes and suggests that restoring HNF4α in hepatocytes responding to chronic injury could successfully restore hepatic function. (9,44) These studies are consistent with a previous observation of decreased periportal HNF4α staining after PH.…”
Section: Discussionmentioning
confidence: 94%
“…Decrease in expression of HNF4α protein after PH resulted in decrease in its transcriptional activity as measured by its target genes, which play a critical role in liver physiology (14). Our observations independently reproduce a microarray study describing decreased HNF4α target gene expression 4 hours post-PH (42). This highlights functional differences between quiescent and proliferating hepatocytes and suggests restoring HNF4α in hepatocytes responding to chronic injury could successfully restore hepatic function (9,43).…”
Section: Discussionsupporting
confidence: 80%
“…Many important genes, such as interleukin-6, c-fos, c-jun, and hepatocyte nuclear factor 4a (HNF-4a), play a vital role in driving hepatocyte entry into cell cycle at the initiation step (Riehle et al, 2011;Jiao et al, 2015). We measured the mRNA levels of these transcripts and found that WZ had no effect on Hnf-4a expression but significantly up-regulated c-jun and c-fos at day1 and day 2, respectively, in PHX/ WZ-treated mice.…”
Section: Discussionmentioning
confidence: 99%